HAK KEKAYAAN INTELEKTUAL DAN INOVASI PERLINDUNGAN HUKUM UNTUK PENGEMBANGAN EKONOMI - Minarti, Tri (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This study examines the role of Intellectual Property Rights (IPR) and innovation as legal protection in economic development. IPR protection is found to have significant economic, social, and legal implications, playing a crucial role in supporting innovation and sustainable economic growth. By protecting intellectual creations, IPR provides incentives for innovators and creators to produce new works, which in turn increases productivity and economic efficiency. This study aims to ; identify the economic, social, and legal implications of IPR protection, analyze the role of IPR in encouraging innovation and sustainable economic growth, evaluate the effectiveness of the IPR protection system in Indonesia and its impact on economic development. This research employed literature review and document analysis.. The analysis was conducted to identify the relationship between IP protection and innovation, as well as its impact on economic growth. A comparative approach was also used to compare the IP protection system in Indonesia with other countries. Conclusion: Intellectual Property Rights (IP) protection has a significant impact on innovation and economic growth. By granting exclusive rights to inventors and creators, IP encourages investment in research and development, creates new jobs, and increases gross domestic product (GDP). Furthermore, IP also contributes to improving public welfare through innovative products and services that enhance the quality of life. In a legal context, a strong IP protection system strengthens legal institutions and provides an effective dispute resolution mechanism. Therefore, strengthening the IP protection system and its enforcement is crucial to supporting sustainable economic development.